Prevalence of hearing impairment among primary school children in rural and urban areas of Aligarh, Uttar Pradesh, India - Parvez, Ashib; Siddiui, Abdur Razzaque; Khan, Zulfia; Hasmi, Shahab F; Khan, Mohammad Shibly (International Journal Of Community Medicine And Public Health, 2017)
Background: Hearing impairment in school children is particularly important because it is the earliest time when the foundation for education and mental and linguistic development is laid down. Present study aims at estimate the burden of hearing impairment among school children in rural and urban field practice areas of Urban and Rural Health Training Centers, JNMCH, AMU, Aligarh, Uttar Pradesh, India. Methods:Estimated sample of 630 was taken. Sampling method: probability proportionate to size (PPS) and stratified random sampling. The children were interviewed using semi structured format followed by general examination and assessment of hearing function. The diagnosis of hearing impairment was done on the basis of history, voice test and abnormal tuning fork tests. It was considered to be present when at least either of the voice test and tuning fork tests was found to be abnormal. Results: The prevalence of Hearing Impairment among the study population was found to be 17.9% (109/610), observed to be higher among rural (18.8%) as compared to urban (13.5%) school children. It was found to be significantly associated with Standard of living Index (SLI) and nutritional status of the children. Conclusions:The study highlights the high burden of hearing impairment in study population and the need for strengthening the school health activities focused on hearing impairment.